Analisis Kinerja Keuangan Pada PT. Gudang Garam Tbk - Elexsi Yosefina Budiyon Poyk (Journal Economic Excellence Ibnu Sina, 2023)
The aim of research at PT. Gudang Garam Tbk is (1) To find out the causes of fluctuations in Profit Loss at PT. Gudang Garam Tbk 2018-2021, (2) To determine the financial performance of PT. Gudang Garam Tbk in terms of the 2018-2021 Liquidity Ratio, (3) To determine the financial performance of PT. Gudang Garam Tbk in terms of the 2018-2021 Solvency Ratio, (4) To determine the financial performance of PT. Gudang Garam Tbk in terms of the 2018-2021 Profitability Ratio. The benefits of this research are (1) for the company, namely to find out the company's financial performance so as to provide an overview and consideration in making financial decisions in the future, (2) for readers to use as a reference in facing similar problems and as a means of knowledge, (3) For the author, namely to increase insight and application of theory. The data collection method used is to study the documentation of the Company's Financial Reports, namely the Balance Sheet, Profit and Loss and other company records from PT Gudang Garam Tbk which are downloaded via the internet. Based on the results of research assessing the performance of PT Gudang Garam Tbk by analyzing financial ratios in its development over the past four years, it is quite stable and healthy because the growth in assets is greater than the growth in debt. (1) The company's current ratio from 2018 to 2020 has increased every year, this proves the growth rate Companies that are growing rapidly are quite good and in 2021 there will be a decline but it can still be said to be quite good. (2) DAR and DER debt ratios in 2018, 2019 and 2021, the company's debt ratio is greater than in 2020. Where in 2020 the debt ratio decreased even though it was still above normal. (3) The ROA profitability ratio increased in 2020 and in 2021 there was a decrease in assets. Meanwhile, ROE reached its lowest point in 2021. However, in 2018 and 2019 it was above the standard average. This proves that the company's ROE is quite good. Based on the conclusions, the author suggests that if liquidity is too high, the company's liquid assets will be excessive and need to be used efficiently to increase profits, so as to avoid being too liquid, the company will have optimal liquidity, the company should maintain financial performance in terms of liquidity ratios, solvency and profitability because the financial performance in 2018 to 2021 was quite good.